2014
DOI: 10.1007/s11418-014-0855-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of a geranylgeranyl diphosphate synthase gene, GGPPS2, isolated from Scoparia dulcis by treatment with methyl jasmonate and yeast extract

Abstract: A cDNA clone, designated SdGGPPS2, was isolated from young seedlings of Scoparia dulcis. The putative amino acid sequence of the translate of the gene showed high homology with geranylgeranyl diphosphate synthase (GGPPS) from various plant sources, and the N-terminal residues exhibited the characteristics of chloroplast targeting sequence. An appreciable increase in the transcriptional level of SdGGPPS2 was observed by exposure of the leaf tissues of S. dulcis to methyl jasmonate, yeast extract or Ca(2+) ionop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On the other hand, GGPPSs were abundantly expressed in leaves when compared with expression in roots. In addition, the present result is consistent with previous data that GGPPSs might be composed of several homologous genes22.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, GGPPSs were abundantly expressed in leaves when compared with expression in roots. In addition, the present result is consistent with previous data that GGPPSs might be composed of several homologous genes22.…”
Section: Resultssupporting
confidence: 93%
“…In the second stage, two GGPP synthases (GGPPSs) from S. dulcis have been cloned and functionally characterized2021. In addition, our previous study revealed that SdGGPS1 and SdGGPS2 were expressed as constitutive and inducible homologous genes, respectively22. However, the enzymes involved in cyclization and modification to produce SDB at the third and fourth stages described above are still unknown, whereas ent -copalyl diphosphate synthase (SdCPS1) has been cloned and functionally characterized23.…”
mentioning
confidence: 99%
“…Plant P450s play an important role in the biosynthesis of secondary metabolites and are often induced by various stresses. In previous reports, it was demonstrated that the biosynthesis of SDB, a tetracyclic diterpene in S. dulcis, is markedly activated by the MJ and yeast extract treatments (Nkembo et al 2005;Yamamura et al 2014). It is clear that a large number of P450s are responsible for not only SDB biosynthesis but also in the other biosynthetic reactions of secondary metabolites in S. dulcis (Yamamura et al 2017).…”
Section: Discussionmentioning
confidence: 99%